2 μm soliton lasers in a bidirectional nonlinear polarization evolution Tm3+-doped fiber oscillator - Ni Feng; Hui Hu; Renlai Zhou; Encai Ji; Xiaoxi Liu; Hongcan Gu; K. Nakkeeran (Results in Physics, 2022)
We experimentally demonstrate a novel 2 μm soliton laser using a bidirectional nonlinear polarization evolution mode-locked Tm3+-doped fiber oscillator. The mode-locking operations between the laser signals propagating in clockwise and counterclockwise directions can be achieved through the intracavity polarization state adjustments independently, and the maximum achieved output powers are 332.5 and 367.8 mW with transfer efficiencies of 17.2 % and 18.3 %, respectively. Hysteresis in the output powers and spectra transformation between the two laser signals propagating in counter directions are observed and investigations are conducted in detail. Benefiting from the robust birefringence filtering effect, the central wavelength of this soliton laser can be continuously tuned from 1951.51 to 2015.89 nm. Stable high-order harmonic mode-locking (HML) operations are observed, and up to 633.02 MHz repetition rate with a central wavelength of 1992.55 nm is achieved. The monitored intensity spectra stability and average output power fluctuations exhibit excellent performance of this proposed 2 μm soliton fiber laser. The phase noise levels in two counter directions propagating light signals are characterized at different average output powers. Our experiment provides a potential technique for the generation of 2 μm solitons fiber laser that can be widely applied in ultrafast time-resolved measurements, mid-infrared frequency metrology, molecular spectroscopy, etc.